Atlantida magazine (1963-1972) - Díaz Hernández, Onésimo (Hispania Nova, 2021)
The journals Cuadernos para el Diálogo, Revista de Occidente and Atlántida were first published in 1963. The first two magazines have received scholarly attention, while the third has yet to be critically analyzed. This article examines Atlántida’s aims, who made them possible, its philosophy, what and how it published. The principal source for this information is the personal archive of the journal’s editor, Florentino Pérez-Embid, housed at the Archivo General of the University of Navarra. I have analyzed the history around the narrative of the journal’s beginnings to its folding in 1972. It appears that Atlántida closed because of the editor’s lack of time to devote to it, as he was also the Director of the Bellas Artes and President of the Universidad Internacional Menéndez Pelayo.
Keywords: Atlántida; culture; magazines; Franco regime; Spain